Preliminary results of biostratigraphic studies of Lower Cretaceous sediments in the Ergel-Khaliv area, SE Mongolia - Uranbileg, Luvsantseden; Purevsuren, Sukhbat; Purevsuren, Byambaa; Enkhbaatar, Batkhuyag; Buyantegsh, Batsaikhan; Ganzorig, Bayasgaa; Zorig, Enkhtaivan; Undarya, Jalbaa (Mongolian Geoscientist, 2020)
The research area is located in the territory of Khatanbulag soum, Dornogovi province, in the Great Govi Province (coordinates: 108°25'39.04"E and 43°10'11.43"N). Here, the authors studied the composition of sediments that had previously been classified as Lower Cretaceous Khukhteeg Formation, forming Mt. Ergel-Khaliv during earlier mapping work. The authors revealed fossils of faunas and floras, processing some data of biostratigraphic survey works taken on fossil-bearing sediments of the area. The fieldwork was conducted in April 2019 by researchers from the Institute of Paleontology, Mongolian Academy of Sciences. The area is very rich in fossils of mollusca, therefore, the local communities named it Dun-Ovoo (Conch hill). During the previous studies, the sediments outcropping around the Ergel-Khaliv were classified as Khukhteeg Formation (K1ht, Aptian-Albian) based on lithological characteristics and comparing them to the type section of the Khukhteeg Formation sediments. Our research revealed biostratigraphic basements and recorded previous data of collected fossils two types of mollusca; we have studied plant fossils, turtles, ostracods, fish and dinosaur bones had been revealed at first in that area. The results of the research work, the fossils that found in the mountain, were amended by more and new types and families of fauna and flora and their constituents. These new findings were helpful in the precise determination of the age of the sediments and provided some information on the paleoenvironmental conditions of the sedimentation period.